Mecanismos de participação e fiscalização do orçamento público: a experiência do orçamento participativo de Vitoria da Conquista - Viana, Mario Augusto Carvalho (2009)
This study aims to perform a research about the participation and inspection mechanisms of the public spending in Vitória da Conquista city, through the experience of Participatory Budgeting. Participation of civil society in the budget cycle is one way of ensuring the exercise of democracy, allowing to identify how civil society can intervene effectively in budget planning, in order to modify the application of public spending, which benefits the most privileged sectors at the expense of the disadvantaged ones, increases the gap between rich and poor people and generates social inequality. Starting with the discussion of the participation and inspection mechanisms of the public spending in Vitória da Conquista city, trying to understand how the exercise of citizenship occurs in the planning, resource allocation and application of participatory budgeting. The methodological aspects applied in this study were developed through a participatory observation, using interviews, in addition to a survey about the history of participatory budgeting in Vitória da Conquista city. Using also the literature that contribute to the understanding of general concepts relevant to the subject. Field research will provide better understanding of how these concepts are applied in practice. As result, we have found that the participatory budget is an enriching experience for the people and the government, since it allows a better understanding about public management and their difficulties in managing the city, helps to participate in the decisions of resource allocation and allows the government to know the differences of the participating regions and their views and a broad knowledge about the problems of each locality